Presumed Choroidal Metastasis of Primary Cutaneous Melanoma: A Case Report - Teele Palumaa; Artur Klett (Case Reports in Ophthalmology)
Introduction: Choroidal metastases most often originate from breast tumors in females and lung cancer in males. Primary cutaneous tumors rarely metastasize to the uveal tract. Case Presentation: Here, we present a rare case of a 47-year-old female patient who was clinically diagnosed with a presumed choroidal metastasis of primary cutaneous melanoma. The patient presented with complaints of decreased vision in her right eye. Her best corrected visual acuity (BCVA) was 0.7 decimal in the right eye and 1.0 in the left eye. Examination revealed a pigmented choroidal lesion in the parafoveal region with a prominence of 2.9 mm, orange pigment on the surface, and subretinal fluid in its projection. She had no history of active malignancy, but at the age of 36, a localized stage IB cutaneous melanoma was removed from her back. Yearly follow-up visits at the dermatologist showed no evidence of active disease. Upon diagnosis of a choroidal tumor, the patient underwent brachytherapy with a ruthenium-106 plaque in the right eye. Follow-up at the oncologist revealed a widespread disease with metastases in distant lymph nodes, liver, lung, pancreas, and brain, an uncommon pattern for primary choroidal melanomas, resembling rather the metastasis pattern of primary cutaneous melanoma. The patient was started on systemic therapy against metastatic cutaneous melanoma. At 21 months after brachytherapy and 19 months after the initiation of systemic anticancer therapy, the patient’s BCVA in the right eye returned to 1.0 decimal, the choroidal lesion reduced in size, and subretinal fluid receded. Two years after the initial presentation, all metastases were stable or decreased in size. Conclusion: This case highlights the possibility of a choroidal metastasis of cutaneous melanoma more than a decade after the first presentation of the disease and highlights the effectiveness of combined brachytherapy and systemic anticancer therapy in managing the disease.